Low Power FDSOI Technology and Devices for RF Applications. (18th August 2016) - Schwan, Christoph; Chew, Kok Wai; Feudel, Thomas; Kammler, Thorsten; Faul, Juergen; Kang, Laegu; Taylor, Richard; Huschka, Andreas; Kluth, Jon; Carter, Rick; McKay, Thomas; Nowak, Edward; et al.
Abstract : We report RF Characteristics in a Low Power High Performance Ultra-thin Body and Box (UTBB) FDSOI technology. The technology features Si-Channel nFETs and SiGe-Channel pFETS, a gate first HiKMG stack with a gate length (LG) of 20nm, BOX thickness (TBOX) of 20nm and is similar to that described previously[1]. The use of the backgate gate is shown to dynamically change the operating range and expand the dynamic range for RF. Competitive fT s are reported for nFETs. The thin body architecture demonstrates high self gain. The technology is shown to be well optimized for applications like IoT where low power and RF performance are a premium.